The Critical Role of RNA m6A Methylation in Cancer - Lan, Qing; Liu, Pei Y.; Haase, Jacob; Bell, Jessica L.; Hüttelmaier, Stefan; Liu, Tao (Cancer research (Chicago, Ill.), 2019)
Since the identification of the first RNA demethylase and the establishment of methylated RNA immunoprecipitation-sequencing methodology 6 to 7 years ago, RNA methylation has emerged as a widespread phenomenon and a critical regulator of transcript expression. This new layer of regulation is termed “epitranscriptomics.” The most prevalent RNA methylation, N6-methyladenosine (m6A), occurs in approximately 25% of transcripts at the genome-wide level and is enriched around stop codons, in 5′- and 3′-untranslated regions, and within long internal exons. RNA m6A modification regulates RNA splicing, translocation, stability, and translation into protein. m6A is catalyzed by the RNA methyltransferases METTL3, METTL14, and METTL16 (writers), is removed by the demethylases FTO and ALKBH5 (erasers), and interacts with m6A-binding proteins, such as YTHDF1 and IGF2BP1 (readers). RNA methyltransferases, demethylases, and m6A-binding proteins are frequently upregulated in human cancer tissues from a variety of organ origins, increasing onco-transcript and oncoprotein expression, cancer cell proliferation, survival, tumor initiation, progression, and metastasis. Although RNA methyltransferase inhibitors are not available yet, FTO inhibitors have shown promising anticancer effects in vitro and in animal models of cancer. Further screening for selective and potent RNA methyltransferase, demethylase, or m6A-binding protein inhibitors may lead to compounds suitable for future clinical trials in cancer patients.